Early Chronic Stress Induced Changes within the Locus Coeruleus in Sporadic Alzheimer’s Disease - Minné, Donné; Marnewick, Jeanine L.; Engel-Hills, Penelope (Current Alzheimer Research, 2023)
Chronic exposure to stress throughout the lifespan has been the focus of many studies on Alzheimer's disease (AD) because of the similarities between the biological mechanisms involved in chronic stress and the pathophysiology of AD. In fact, the earliest abnormality associated with the disease is the presence of phosphorylated tau protein in locus coeruleus neurons, a brain structure highly responsive to stress and perceived threat. Here, we introduce allostatic load as a useful concept for understanding many of the complex, interacting neuropathological changes involved in the AD degenerative process. In response to chronic stress, aberrant tau proteins that begin to accumulate within the locus coeruleus decades prior to symptom onset appear to represent a primary pathological event in the AD cascade, triggering a wide range of interacting brain changes involving neuronal excitotoxicity, endocrine alterations, inflammation, oxidative stress, and amyloid plaque exacerbation. While it is acknowledged that stress will not necessarily be the major precipitating factor in all cases, early tau-induced changes within the locus coeruleus-norepinephrine pathway suggests that a therapeutic window might exist for preventative measures aimed at managing stress and restoring balance within the HPA axis.
Keywords: LC